Formulation and Effectiveness Test of Red Ginger (Zingiber officinale var. Rubrum) and Starfruit (Averrhoa bilimbi L.) Combination Shampoo Against Pediculus humanus capitis - Anindita, Reza; Harahap, Salwa Zhafarina; Beandrade, Maya Uzia; Putri, Intan Kurnia (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Some of the natural ingredients that have the potential to be developed into a health product for pediculosis are red ginger (Zingiber officinale var. Rubrum) and star fruit (Averrhoa bilimbi L.). Secondary metabolite compounds in red ginger extract and star fruit that can potentially kill head lice Pediculosis humanus capitis include alkaloids, flavonoids, and saponins. The purpose of this study was to determine the physical fitness and effectiveness of the lethal power of the combination of red ginger extract and star fruit with formula 1 (F1) 1.5%, formula 2 (F2) 2%, and Formula 3 (F3) 2.5%. The tests carried out were phytochemical screening tests (alkaloids, tannins, saponins, and flavonoids), physical stability of shampoo (organoleptic, homogeneity, foam height, viscosity, and pH) for four weeks of storage, and testing the effectiveness of shampoo killing power against head lice Pediculus humanus capitis. Data analysis was carried out descriptively and comparatively using one-way ANOVA. Phytochemical screening of red ginger extract and star fruit was positive for alkaloids, tannins, saponins, and flavonoids. The organoleptic test of the shampoo on all three formulas produced a light brown colour, a distinctive aroma of lemon oil, and a thick shape. The homogeneity test showed a homogeneous shampoo preparation. F1 foam level test (7.7-11 cm), F2 (7.3-11 cm), and F3 (7.2-11 cm). F1 viscosity test (2,010-2,020 cps); F2 and F3 (2,020 cps). One-way ANOVA pH F1 test (8.54-8.77); F2 (8.01-8.70); F3 (8.61-8.77) and One-way ANOVA results for pH values obtained significant values of 0.096 > 0.05, while the killing power of aphids was 0.02 < 0.05. The three shampoo formulas of red ginger extract and star fruit showed good physical evaluation and still entered the test requirement range for four weeks of storage. Based on the results of statistical analysis, it was shown that the variation in the concentration of the formula did not cause a change in pH during four weeks of storage. The administration of a combination shampoo of red ginger extract and star fruit with a formulation of F1 1.5%, F2 2%, and F3 2.5% was able to have a natural effect on the average number of head lice deaths of Pediculus humanus capitis.